PERENCANAAN PRODUKSI KERUPUK PULI DENGAN METODE PROGRAM DINAMIK DI UD RIZKY JEMBER - Bambang Herry Purnomo; Yuli Wibowo; Kiswatul Maulidiah (AGROINTEK, 2015)
Production planning is an area that is very important in making the decision of the level of startegis company, Especially in manufacturing companies.The production has an important role in the production of processing facilities, because it includes equipment, resources and labor for some operations. Production planning done aims to give a decision based on resources owned companies in the meet demand for products produced. UD Rizky is industry of cracker which is in kabupaten jember. Production planning conducted by UD Rizky is not optimal, So as to cause a mismatch between demand market with the amount of supplies, and the production. The purpose of this research is to produce production planning cracker optimal production includes the number and the amount of supplies in the period october 2014 until september 2015. The methodology that was used as solution optimal for determining the amount of the production and the number of supplies cracker is a method of dynamic programming with the function of the objective of minimizing the cost of production during the period a year. The results of research indicates that production planning using dynamic programming can minimize the amount of supplies worth 1,200 kg and the production of 11,993 kg. Besides, production planning using methods dynamic programming at UD Rizky jember may lower production costs amounting to 32,51 % from Rp 334.327.982 to Rp 225.630.659.